Boundary Condition/Examples/Arbitrary Example 1

From ProofWiki
Jump to navigation Jump to search

Example of Boundary Condition

Consider the differential equation:

$\dfrac {\d^2 y} {\d x^2} + 4 \dfrac {\d y} {\d x} = 0$

for $x \ge 0$.

From Solution to $y'' + 4 y' = 0$ this has a general solution:

$y = A + B e^{-4 x}$


Let the boundary conditions be:

\(\ds y\) \(=\) \(\ds 0\) when $x = 0$
\(\ds \dfrac {\d y} {\d x}\) \(=\) \(\ds 1\) when $x = 0$


Then substituting $x = 0$ into the general solution and its first derivative yields:

\(\ds A\) \(=\) \(\ds \dfrac 1 4\)
\(\ds B\) \(=\) \(\ds -\dfrac 1 4\)

and so the particular solution:

$4 y = 1 - e^{-4 x}$


Sources